Discovery of the Elusive Carbonic Acid (HOCOOH) in Space - Miguel Sanz-Novo; Víctor M. Rivilla; Izaskun Jiménez-Serra; Jesús Martín-Pintado; Laura Colzi; Shaoshan Zeng; Andrés Megías; Álvaro López-Gallifa; Antonio Martínez-Henares; Sarah Massalkhi; Belén Tercero; Pablo de Vicente; et al. (The Astrophysical Journal, 2023)
A quarter century after the detection of the last interstellar carboxylic acid, acetic acid (CH _3 COOH), we report the discovery of a new one, the cis-trans form of carbonic acid (HOCOOH), toward the Galactic center molecular cloud G+0.693–0.027. HOCOOH stands as the first interstellar molecule containing three oxygen atoms and the third carboxylic acid detected so far in the interstellar medium. Albeit the limited available laboratory measurements (up to 65 GHz), we have also directly identified several pairs of unblended lines in the astronomical data (between 75 and 120 GHz), which allowed us to slightly improve the set of spectroscopic constants. We derive a column density for cis-trans HOCOOH of N = (6.4 ± 0.4) × 10 ^12 cm ^−2 , which yields an abundance with respect to molecular H _2 of 4.7 × 10 ^−11 . Meanwhile, the extremely low dipole moment (about 15 times lower) of the lower-energy conformer, cis-cis HOCOOH, precludes its detection. We obtain an upper limit to its abundance with respect to H _2 of ≤1.2 × 10 ^−9 , which suggests that cis-cis HOCOOH might be fairly abundant in interstellar space, although it is nearly undetectable by radio astronomical observations. We derive a cis-cis / cis-trans ratio of ≤25, consistent with the smaller energy difference between both conformers compared with the relative stability of trans- and cis -formic acid. Finally, we compare the abundance of these acids in different astronomical environments, further suggesting a relationship between the chemical content found in the interstellar medium and the chemical composition of the minor bodies of the solar system, which could be inherited during the star formation process.